2019
DOI: 10.1111/jocd.12960
|View full text |Cite
|
Sign up to set email alerts
|

The psychological and aesthetic impact of age‐related hair changes in females

Abstract: Background While dermatologists focus on practices to promote anti‐aging, thinning hair that frames a more rejuvenated face can affect age perception and cosmesis. Objectives To characterize the effects of age‐related hair changes on age determination and perceived attractiveness. Methods A search was conducted for articles on intrinsic and extrinsic aging as it relates to hair. Key studies on the hair aging process and its effects on self‐perception, confidence, and anti‐aging were reviewed. Results According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 100 publications
(259 reference statements)
0
17
0
Order By: Relevance
“…Female pattern AGA is considered a common hair disorder that starts in the third decade of life, reaching its peak after the age of 50 years. AGA may affect up to 40% of women at some point in their life, with significant effects on quality of life ( Ahluwalia and Fabi, 2019 ). Different medications, such as minoxidil (2% or 5%), flutamide, dutasteride, finasteride, and spironolactone, as well as cosmetic hair procedures, including hair transplantation, are the existing treatment options for AGA.…”
Section: Discussionmentioning
confidence: 99%
“…Female pattern AGA is considered a common hair disorder that starts in the third decade of life, reaching its peak after the age of 50 years. AGA may affect up to 40% of women at some point in their life, with significant effects on quality of life ( Ahluwalia and Fabi, 2019 ). Different medications, such as minoxidil (2% or 5%), flutamide, dutasteride, finasteride, and spironolactone, as well as cosmetic hair procedures, including hair transplantation, are the existing treatment options for AGA.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] A recent review on psychological and aesthetic impact of age-related hair changes in women showed hair loss to demonstrably affect a woman's perceived age and psychosocial wellbeing. 6 Increasing with age and menopause, 7 the most commonly diagnosed alopecia is female pattern hair loss (FPHL), also known as androgenetic alopecia (AGA), which affects an estimated 40% of women over 60. 8 The complex pathophysiology of FPHL is not yet fully elucidated, but is now considered to be only partly related to androgens, with growing evidence suggesting it's multifactorial.…”
Section: Introduction Hmentioning
confidence: 99%
“…7,10 There are likewise age-related changes in hair diameter and density that are independent of menopause, but occur at approximately the same time, compounding the perception of hair loss for middle-aged women. 6,11 Hair loss and thinning in women is polygenic and multi-factorial, with contribution from environmental factors such as aging, stress, and inflammation. 4,6,9 Nevertheless, there is a paucity of controlled studies assessing interventions for hair thinning in menopausal women.…”
Section: Introduction Hmentioning
confidence: 99%
See 2 more Smart Citations